Pengaruh Risiko Sistematis, Leverage, Dan Likuiditas Terhadap Return Saham Lq 45 Yang Terdaftar Pada Bursa Efek - Chandra Ferdinand Wijaya; Hamfri Djajadikerta (Ultima Management : Jurnal Ilmu Manajemen, 2017)
Investors want high stock return to increase wealth from their stock investment. In determining stocks that can provide high returns, there are factors that must be considered. LQ 45 stocks are identical to profitable and high return stock. In fact, LQ 45 stocks do not always benefit investors. There are risk factors that influence LQ 45 stock return, which is the market risk and fundamental risk. Market risk is known as systematic risk and fundamental risk is reflected through companies’ liquidity and leverage. There are inconsistencies over the influence of this variables on stock return. Therefore, the purpose of this research is to examine the effect of systematic risk, leverage, and liquidity on stock return. This research is a causal research and conducted on LQ 45 companies during 2011- 2015. This research uses simple random sampling as sampling method. Systematic risk is measured by stock beta coefficients, leverage is measured by Debt to Equity Ratio, and liquidity is measured by Current Ratio. Research’s result shows that systematic risk, leverage, and liquidity have significant effect on stock return simultaneously. Partial test shows that systematic risk has insignificant effect on stock return, while leverage and liquidity have positive significant effect on stock return. Keywords: Systematic risk, leverage, liquidity, stock return, LQ 45